2013
DOI: 10.1128/jvi.03327-12
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Decapping Activators LSm1, Pat1, and Dhh1 Control the Ratio of Subgenomic to Genomic Flock House Virus RNAs

Abstract: , and Dhh1 control the ratio of subgenomic RNA3 to genomic RNA1 production, a key feature in the FHV life cycle mediated by a long-distance base pairing within RNA1. Depletion of LSM1, PAT1, or DHH1 dramatically increased RNA3 accumulation during replication. This was not caused by differences between RNA1 and RNA3 steady-state levels in the absence of replication. Importantly, coimmunoprecipitation assays indicated that LSm1-7, Pat1, and Dhh1 interact with the FHV RNA genome and the viral polymerase. By using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Confirmation of this hypothesis will have to await development of an experimental system that allows specific detection of RNA3, and we are currently in the process of designing suitable probes to that end. Interestingly, it was recently shown that the cellular decapping activators LSm1, Pat1, and Dhh1 are involved in FHV RNA replication in yeast and control the ratio of FHV RNA1 to subgenomic RNA3 (47). These decapping activators are known P-body components, and they may be poised for additional roles in the absence of a functional B2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of this hypothesis will have to await development of an experimental system that allows specific detection of RNA3, and we are currently in the process of designing suitable probes to that end. Interestingly, it was recently shown that the cellular decapping activators LSm1, Pat1, and Dhh1 are involved in FHV RNA replication in yeast and control the ratio of FHV RNA1 to subgenomic RNA3 (47). These decapping activators are known P-body components, and they may be poised for additional roles in the absence of a functional B2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that the decapping activator Lsm1-7-Pat1 complex is exploited by BMV to sequentially regulate translation and replication of the viral genomes. Given the common replication strategies of (+)RNA viruses, the dependence on Lsm1-7-Pat1 complex for replication of at least four (+)RNA viruses infecting plants, insects, and humans and the dependence on Hfq, a homolog of Lsm1 in bacteria, for replication of the bacteriophage Qβ (Franze de Fernandez et al 1968;Diez et al 2000;Mas et al 2006;Scheller et al 2009;Chahar et al 2013;Gimenez-Barcons et al 2013), it is likely that these complexes are broadly used within this viral group by similar mechanisms as the ones described here. Moreover, the obtained results uncover functionalities of these versatile complexes that might provide novel insights into their essential role in cellular mRNA decay, since it also requires sequential binding and post-binding steps that are still not understood.…”
mentioning
confidence: 99%
“…Interestingly, in contrast to its decay function on cellular mRNAs, we and others have previously shown that the Lsm1-7-Pat1complex plays a fundamental role in the life cycle of a wide range of positive-strand RNA [(+)RNA] viruses including the plant Brome mosaic virus (BMV), the animal Flock House virus, the human Hepatitis C virus (HCV) and the emerging West Nile virus (WNV) (Diez et al 2000;Mas et al 2006;Scheller et al 2009;Chahar et al 2013;Gimenez-Barcons et al 2013). After these viruses enter the host cell, their single-stranded RNA genomes act as mRNAs and are directly translated to express the viral proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity of the FHV genome, combined with the advantages of yeast genetics make the FHV-yeast system another excellent model system to study basic aspects of (+)RNA biology, including virus–host interactions. Interestingly, three of the highly conserved host factors subverted by FHV are the decapping activators Lsm1–7, Pat1 and Dhh1 [48]. …”
Section: The Flock House Virus Subverts Features Of Decapping Protmentioning
confidence: 99%
“…This latter activity is essential for proper and timely expression of the different viral proteins throughout the different stages of the viral life cycle. Interestingly, depletion of Lsm1–7, Pat1 or Dhh1 disrupts this activity and alters the RNA1/RNA3 ratio [48]. …”
Section: The Flock House Virus Subverts Features Of Decapping Protmentioning
confidence: 99%